2012
DOI: 10.1152/ajprenal.00189.2011
|View full text |Cite
|
Sign up to set email alerts
|

The pendrin anion exchanger gene is transcriptionally regulated by uroguanylin: a novel enterorenal link

Abstract: The pendrin/SLC26A4 Cl(-)/HCO(3)(-) exchanger, encoded by the PDS gene, is expressed in cortical collecting duct (CCD) non-A intercalated cells. Pendrin is essential for CCD bicarbonate secretion and is also involved in NaCl balance and blood pressure regulation. The intestinal peptide uroguanylin (UGN) is produced in response to oral salt load and can function as an "intestinal natriuretic hormone." We aimed to investigate whether UGN modulates pendrin activity and to explore the molecular mechanisms responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Furthermore, it is demonstrated that multiple plasma membrane transporters, such as SLC26a6 and NBCe1 (a basolateral Na ϩ /HCO 3 Ϫ -contransporter), in addition to apical CFTR or NKCC1, may be acted on by the guanylin peptides, based on the observed inhibition of HCO 3 Ϫ secretion. Indeed, a recent study revealed that UGN injected into mice resulted in decreased mRNA and protein expression of renal pendrin/SLC26a4, another Na ϩ / HCO 3 Ϫ cotransporter (51). Future studies should examine if the guanylin peptides affect the activity of SLC26a6 and NBCe1.…”
Section: Perspectives and Significancementioning
confidence: 98%
“…Furthermore, it is demonstrated that multiple plasma membrane transporters, such as SLC26a6 and NBCe1 (a basolateral Na ϩ /HCO 3 Ϫ -contransporter), in addition to apical CFTR or NKCC1, may be acted on by the guanylin peptides, based on the observed inhibition of HCO 3 Ϫ secretion. Indeed, a recent study revealed that UGN injected into mice resulted in decreased mRNA and protein expression of renal pendrin/SLC26a4, another Na ϩ / HCO 3 Ϫ cotransporter (51). Future studies should examine if the guanylin peptides affect the activity of SLC26a6 and NBCe1.…”
Section: Perspectives and Significancementioning
confidence: 98%
“…Of these 5 protein coding transcripts, only the one (Ensemble transcript ID# ENST00000265715) encoding a 780 amino acid long protein (from 21 exons) was originally linked to Pendred Syndrome [4]. Since then, the promoter controlling this particular open reading frame has been the subject of many investigations [18,23,30,31,32,33,34,35,36,37,38], as well as the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Considering the major role of both guanylin peptides and pendrin in the regulation of total body NaCl content, maintenance of extracellular fluid volume and control of blood pressure, we investigated UGN modulation of pendrin expression and explored the molecular mechanisms responsible for this modulation [81]. …”
Section: The Anion Exchanger Pendrinmentioning
confidence: 99%
“…UGN also decreased endogenous pendrin mRNA levels in HEK293 cells [81]. We next examined possible modulation by UGN of human PDS ( hPDS ) transcription at the level of the hPDS promoter [81]. …”
Section: The Anion Exchanger Pendrinmentioning
confidence: 99%